Assessing Fidelity to Suicide Reporting Guidelines in Canadian News Media: The Death of Robin Williams. (May 2017) - Creed, Michael; Whitley, Rob
Objective: Mindset is a short recently-published booklet funded by the Mental Health Commission of Canada outlining evidence-based guidelines and best practices for journalists writing about mental health and suicide. Our study aimed to assess fidelity to Mindset recommendations in Canadian newspaper reports of a recent celebrity suicide. A secondary aim is to identify common themes discussed in these newspaper articles. Methods: Articles about Robin Williams' suicide from major Canadian newspapers were gathered and coded for presence or absence of each of the 14 recommendations in the "Covering Suicide" section of Mindset . A threshold of 80% was set to test for high fidelity to the guidelines. A qualitative content analysis of the articles was also undertaken to discern common themes and social issues discussed in the articles. Results: Fifty-five per cent of articles surpassed the 80% threshold for high fidelity, while 85% applied at least 70% of the recommendations. The recommendation most commonly overlooked was "Do tell others considering suicide how they can get help, " which was absent in 73% of articles. The most common themes discussed were those of addictions and stigma. Conclusions: The news articles generally follow the evidence-based guidelines regarding the reporting of suicide set out in Mindset . This is a welcome development. Future research should continue to examine reporting of suicide to assess for further improvements, while also examining the wider impact of Mindset on the reporting of mental illness per se.